Predição de cobertura radioelétrica em terrenos mistos: uma abordagem via equações integrais - Claudio Garcia Batista (2008)
This work deals with electromagnetic wave propagation in the VHF and UHF bands, motivated by the need for more accurate radio communication prediction for wireless networks planning. An integral equation based formulation is developed considering the terrain as inhomogeneous and the ground losses are estimated by Leontovich boundary condition. Approximations extensively discussed in the scienti c literature have been adopted: electrically smooth ground, perpendicular invariant along the propagation direction terrain, neglect of back-scattering and near-grazing incidence. These equations are solved using the Method of Moments (MoM) numerical technique. The integral equation based model leads to a high order linear system and consumes an overwhelming computational e ort. The FAFFA (Fast Far Field Approximation) accelerating technique is applied in the formulation in order to speed up the process and allow a greater practical application of the model. The application of FAFFA tremendously reduces the processing time of the algorithm, achieving computational savings of the order of 97 % . e compared and discussed, as well as the performance of the technique FAFFA. The model recently published by the ITU (International Telecommunication Union), the Recommendation ITU-R 1546-2, is presented and its main calculation methods discussed. A prediction software named MACNEE (Maquina para Calculo Numerico de Espalhamento Eletromagnetico) was developed for the implementation of the models discussed. Two study cases are analyzed: the rst involves ve pro les located in Denmark, and the second case presents measures obtained around the Paranoa lake in Brasilia. The results of the models are compared and discussed, as well the performance of the FAFFA technique.